Association between Upper-airway Surgery and Ameliorative Risk Markers of Endothelial Function in Obstructive Sleep Apnea - Fan Wang (Nature Portfolio, 2019)
Abstract The objective of our study was to evaluate the effects of upper-airway surgery on improvement of endothelial function-related markers in patients with obstructive sleep apnea (OSA). Subjects with moderate to severe OSA who underwent upper-airway surgery, with a follow-up duration of at least 6 months, were included. Pre- and postoperative polysomnographic variables and endothelial function-related markers were compared. Subgroup and correlation analyses were conducted to find possible indicators for better endothelial function-related markers after upper-airway surgery. In total, 44 patients with OSA were included. The mean follow-up duration was 1.72 ± 0.92 years. Serum VEGFA [−20.29 (CI: −35.27, −5.31), p < 0.05], Ang2 [−0.06 (CI: −0.16, 0.03), p < 0.05], E-selectin [−7.21 (CI: −11.01, −3.41), p < 0.001], VWF [−58.83 (CI: −103.93, −13.73), p < 0.05], VWFCP [−33.52 (CI: −66.34, −0.70), p < 0.05], and TM [−0.06 (CI: −0.09, −0.03), p < 0.05] were significantly lower after upper-airway surgery. However, other risk markers of endothelial function, such as Ang1, ICAM1, VEGFR1, and VCAM, did not change significantly. Correlations between improved endothelial function-related markers and ameliorated oxyhemoglobin saturation and glucolipid metabolism were established. Upper-airway surgery might be associated with an improvement in endothelial function in patients with OSA. These changes may be associated with improved oxygen saturation after upper-airway surgery.